Multiplane two-dimensional strain echocardiography for segmental analysis of right ventricular mechanics - Greiner, Sebastian; Heimisch, Melissa; Aurich, Matthias; Heß, Alexander; Katus, Hugo; Mereles, Derliz (Clinical research in cardiology, 2014)
Recent studies showed the prognostic value of strain measurements of the free right ventricular (RV) wall. The aim of this study was to evaluate the feasibility and the diagnostic value of the assessment of longitudinal mechanics of all segments of the RV by multiplane, two-dimensional transthoracic (2D) strain echocardiography.
Gesehen am 22.07.2020